2022
DOI: 10.3389/fpls.2021.830390
|View full text |Cite
|
Sign up to set email alerts
|

The FtsH-Inactive Protein FtsHi5 Is Required for Chloroplast Development and Protein Accumulation in Chloroplasts at Low Ambient Temperature in Arabidopsis

Abstract: Chloroplasts are indispensable for higher plants. The growth and development of plants are very sensitive to environmental temperature changes, and chloroplast development is also regulated by adverse environmental temperatures. However, the molecular mechanism of how plants coordinate chloroplast development and environmental temperature changes remains largely unknown. Here, a temperature-conditioned chloroplast development defective mutant thermo-sensitive mutant in leaf color 2 (tsl2) of Arabidopsis was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Chlorophyll levels fluctuated significantly under low-light environments, as their biosynthesis required the participation of catalytic enzyme genes, such as CHLI and PPOX, which were highly expressed in the present study [74,75]. Other DEGs related to chloroplast development and Chlorophyll synthesis were also collected, such as DCL, RPL21c, DAG, SG1, FtsHi5, and Tic110 [76][77][78][79][80][81]. Furthermore, the introns-splicing-related DEGs, such as PPRs, CFM3, MTERF4, and MTERF5, were also upregulated in this study.…”
Section: Photosynthesis-related Degs In Eshu 10 Play An Important Rol...mentioning
confidence: 59%
“…Chlorophyll levels fluctuated significantly under low-light environments, as their biosynthesis required the participation of catalytic enzyme genes, such as CHLI and PPOX, which were highly expressed in the present study [74,75]. Other DEGs related to chloroplast development and Chlorophyll synthesis were also collected, such as DCL, RPL21c, DAG, SG1, FtsHi5, and Tic110 [76][77][78][79][80][81]. Furthermore, the introns-splicing-related DEGs, such as PPRs, CFM3, MTERF4, and MTERF5, were also upregulated in this study.…”
Section: Photosynthesis-related Degs In Eshu 10 Play An Important Rol...mentioning
confidence: 59%
“…The identified genes may be related to environmental conditions (i.e., response to high altitude, drought and salinity) and reproductive divergence (e.g., pollen tube growth and flowering) between the two species (Table S7). For example, among significantly divergent genes with selection signatures, we found four ( GRF4 , PSUT , FTSHI and PIF1 ) related to cold response (Jiang et al, 2020; Lantzouni et al, 2020; Li et al, 2022; Patzke et al, 2019) and six ( RAD23C , CHR24 , ALY3 , RECQ4A , RAD7 and BSD ) associated with nucleotide excision‐repair and DNA‐damage tolerance (Hacker et al, 2022; Kunz et al, 2005; Lahari et al, 2018; Lang et al, 2021; Shaked et al, 2006). These genes may be important for the adaptation of M. archiducis‐nicolai to high‐altitude environments.…”
Section: Discussionmentioning
confidence: 98%
“…The identified genes may be related to environmental conditions (i.e., response to high altitude, drought and salinity) and reproductive divergence (e.g., pollen tube growth and flowering) between the two species (Table S7). For example, among significantly divergent genes with selection signatures, we found four (GRF4, PSUT, FTSHI and PIF1) related to cold response (Jiang et al, 2020;Lantzouni et al, 2020;Li et al, 2022;Patzke et al, 2019) and six (RAD23C, CHR24, ALY3, RECQ4A, RAD7…”
Section: Genomic Islands Of Divergence and Ecological Adaptationmentioning
confidence: 99%
“…Interestingly, a recent study showed that Tic236, a large TIC component constantly linking the TIC and TOC complex, also plays a role in chloroplast division ( Chen et al., 2018b ; Fang et al., 2022 ), providing a hint for the connection of these two processes. The depletion of FtsHi5 results in hypersensitivity to decreased ambient temperature ( Li et al., 2021 ), which has also been observed in many mutants with disrupted chloroplast proteostasis ( fug1 , prps17 , prpl11 , and var2 ; Marino et al., 2019 ), indicating a close link between chloroplast proteostasis and temperature stress.…”
Section: Elimination Of Chloroplast Proteinsmentioning
confidence: 88%